Enhancement of human periodontal ligament by preapplication of orthodontic loading - Kittitat Nakdilok (2020)
© 2019 American Association of Orthodontists Introduction: The quantity of remaining periodontal ligament (PDL) on the root surface of donor teeth is essential for the success of tooth autotransplantation. Preapplication of orthodontic loading increases this quantity on rat tooth root surfaces. However, little is known about the effects of preloading on human PDL or the ease of tooth extraction. This study aimed to determine the optimal duration of preloading for enhanced PDL on the root surface of extracted human premolars and for facilitating extraction. Methods: Sixty patients received orthodontic preloading with a bracket connected to an archwire on one of their maxillary first premolars for 2, 4, 6, or 8 weeks, whereas the contralateral premolar was not loaded as a control. Premolar extractions were performed with a record of the duration and difficulty of extraction. The extracted premolars were fixed and stained with toluidine blue. Digitized images were recorded under a stereomicroscope, and the percentage of stained PDL was analyzed. Results: Orthodontic preloading for 4, 6, and 8 weeks significantly increased the percentage of stained PDL on the root surface compared with the control (P <0.05). The duration and difficulty of extraction were significantly less in preloaded than that of unloaded teeth after 4, 6, and 8 weeks (P <0.05). Conclusions: A 4-week duration of orthodontic preloading is suggested as the shortest duration to adequately enhance PDL and ease tooth extraction; both outcomes may be beneficial for tooth autotransplantation.